Metabolic Reprogramming of Cancer-Associated Fibroblasts by IDH3α Downregulation - Zhang, Daoxiang; Wang, Yongbin; Shi, Zhimin; Liu, Jingyi; Sun, Pan; Hou, Xiaodan; Zhang, Jian; Zhao, Shimin; Zhou, Binhua P.; Mi, Jun (Cell reports (Cambridge), 2015)
Cancer-associated fibroblasts (CAFs) provide critical metabolites for tumor growth and undergo metabolic reprogramming to support glycolysis. However, the molecular mechanisms responsible for this change remain unclear. Here, we report that TGF-β1- or PDGF-induced CAFs switch from oxidative phosphorylation to aerobic glycolysis. We identify downregulation of isocitrate dehydrogenase 3α (IDH3α) as a marker for this switch. Furthermore, miR-424 downregulates IDH3α during CAF formation. Downregulation of IDH3α decreases the effective level of α-ketoglutarate (α-KG) by reducing the ratio of α-KG to fumarate and succinate, resulting in PHD2 inhibition and HIF-1α protein stabilization. The accumulation of HIF-1α, in turn, promotes glycolysis by increasing the uptake of glucose, upregulating expression of glycolytic enzymes under normoxic conditions, and inhibiting oxidative phosphorylation by upregulating NDUFA4L2. CAFs from tumor samples exhibit low levels of IDH3α, and overexpression of IDH3α prevents transformation of fibroblasts into CAFs. Our studies reveal IDH3α to be a critical metabolic switch in CAFs. [Display omitted] •IDH3α is uniformly decreased in CAFs•Downregulation of IDH3α promotes metabolic switch to glycolysis in CAFs•Decreased IDH3α reduces the ratio of α-KG to fumarate and succinate•Reduced α-KG leads to the stabilization of HIF-1α under normoxic conditions Zhang et al. provide conclusive evidence that CAFs are prone to glycolysis and that this metabolic change is responsible for the tumor-promoting effect of CAFs. In addition, their study identifies a detailed molecular mechanism underlying glycolytic reprogramming in CAFs.